Integration theory and the problems of integration policy in the Third World - Volker Nienhaus (Intereconomics, 1987)
The many groupings of developing countries formed in the fifties and sixties with a view to establishing a customs union have failed to achieve convincing results so far. Would another integration strategy have been more successful?
Keywords: 330